Edward Hopper : an intimate biography - Levin, Gail, 1948- (University of California Press, 2023)
New York Times Notable Book Los Angeles Times Book Prize Finalist Wall Street Journal--One of Five Best Artist Biographies Edward Hopper's canvasses are filled with stripped-down spaces and unrelenting light, evocative landscapes, and the lonely aspects of men and women seemingly isolated in their surroundings. What kind of man had this haunting vision, and what kind of life engendered t.